Introduction to the special issue on the HEALing Communities Study. (1st December 2020) - El-Bassel, Nabila; Jackson, Rebecca D.; Samet, Jeffrey; Walsh, Sharon L.
Highlights: Collection of papers introducing design and implementation of HEALing Communities Study. Overview of how to reduce opioid overdose deaths nationally and locally. Describes the diversity and burden of overdose in HCS communities. Abstract: The severity of the overdose epidemic underscores the urgent need for innovative and high impact interventions that promote the rapid penetration and scale up of evidence-based practices (EBPs) in communities profoundly affected by fatal opioid overdose. This special issue shares scientific advancements in implementation research design and evaluation of a novel data-driven community-based intervention. The HEALing (Helping End Addiction Long-Term) Communities Study (HCS) is a four-year study that is designed to examine the effectiveness of the Communities That HEAL (CTH) intervention. The CTH intervention supports the dissemination of EBPs in 67 communities across four high-burdened states—Kentucky, Massachusetts, New York, and Ohio. The diversity in these communities in terms of rural-urban status, race-ethnicity and other social determinants of health facilitates generalizability of results to other communities across the US. The nine papers in this special issue describe critical elements that constitute the HCS framework and design. This includes the implementation of EBPs that have a substantial impact on fatal and non-fatal opioid overdose, the Opioid-overdose Reduction Continuum of Care Approach, communication campaigns to increase awareness and demand for EBPs and reduce stigma against people with OUD and MOUD interventions, and the process of community engagement. This includes how to form community coalitions and gain their commitment, and steps taken to mobilize coalitions to pursue EBP implementation and ensure EBPs are adapted for community needs. The collective papers in this issue demonstrate that the design of any complex study must adapt to unanticipated temporal events, including the rapidly emerging COVID-19 crisis. Readers will learn about the scientific process of the design and implementation of a community-engaged intervention, its methodologies, guiding conceptual models, and research implementation strategies that can be applied to address other health issues.